Witkacowskie raje - Tomassucci, Giovanna (Wydawnictwo Naukowe UAM w Poznaniu, 2010)
The studies on Witkacy’s oeuvre Narcotics (Narkotyki, 1932) exist without any specific status, as if reduced to a research element ancillary to other “more serious” creative areas of its author. The above is especially astonishing since they belong to a specific literary genre which was started with De Quincy’s Confessions of an Opium Eater (1821) and became really successful in the 19th and 20th centuries, with Baudelaire, Cocteau, Artaud, Huxley and many others. Witkacy was the first Polish writer who addressed the issue of drug addiction and wrote explicitly on the role of narcotics in artistic creation. He experimented with cocaine, mescaline, peyotl and discovered “the magic peyotl” in the same years as A. Artaud and W. Benjamin, and many years before Huxley. He was also one of the few writers who, after having experimented with drugs, began to deal with the theory of narcotics. The use of opium, cocaine, dawamesk also became a sort of caricatural form in many of his works from Cuttlefish (Mątwa) up to the novel The Only Way Out (Jedyne wyjście). The aim of my work is to try to answer several questions: In what way does the author’s interest in the addiction of Unwashed Souls (Niemyte dusze) fit into the 19th and 20th century debate between doctors, writers and European artists? Can Witkacy’s literary and dramatic work demonstrate that he was familiar with publications on pharmacology (published in Germany and France in the 20s) and also with the authors who were writing about drugs in the 19th and 20th century? How does his prohibitionist point of view fit with his historiosophy? Can Narcotics be considered a literary work? I have also tried to determine the anonymous sources quoted by Witkacy and co-authors of Narcotics, B. Filipowski and S. Glass (pen name of Dezydery Prokopowicz).
Witkacy’s Paradises